Shell-thickness dependent Fano resonance in molecular catalyst functionalized CdSe/ZnS core/shell QDs - Gebre, Sara T. (2025)
Hybrid photocatalysts consisting of molecular catalyst functionalized semiconductors have attracted intense recent interest in solar fuel applications. Charge transfer interactions between the molecular catalyst and semiconductor have been long recognized to affect catalyst properties by controlling photoinduced charge separation across the semiconductor/molecule interface. In this paper, we investigate how such an interaction can also affect Fano resonance between the catalyst vibration and the intraband absorption of semiconductors. Using [Re(3,3’-disulfide-2,2’- bipyridine)(CO)3Cl] (ReS2) functionalized CdSe/ZnS core/shell QDs as a model system, we show that the CO stretching mode of the catalyst can interact with the broad intraband absorption of conduction band electrons. Detailed analysis shows that the Fano resonance asymmetry factor q, decreases at larger ZnS shell thickness. This experimental finding is consistent with a theoretical model that assumes that the vibronic interaction leading to the observed Fano resonances is mediated by effective charge transfer interactions between the QD conduction band electron and adsorbed catalyst. Because of the Type I band alignment in the CdSe/ZnS QDs, an increasing shell thickness leads to a decreasing CB electron density at the ZnS shell surface, reducing electronic coupling and the charge transfer interaction with the adsorbed catalysts.